Propriedade de um nitossolo vermelho após nove anos de uso de sistemas de manejo e efeito sobre culturas - Veiga, Milton da (2005)
Long-term use of management systems result in alteration in physical and chemical soil properties and its intensity is related to time, soil and climate conditions. Physical properties are more susceptible to changes by the tillage system, while chemical properties by the residue management and nutrient application, resulting in different responses of crops growth and yield. This study was performed in order to evaluate long-term effect of applying soil tillage systems (NT = no-till; CP = chisel plow + 1 secondary disking; CT = primary + 2 secondary disking; CTb = CT with crop residues burned; and CTr = CT with crop residues removed from the field) and nutrient sources (C = control, without nutrient application; MF = mineral fertilizers according official recommendation for each crop; PL = 5 Mg ha-1 of wet matter of poultry litter; CM = 60 m3 ha-1 of liquid cattle manure; and SM = 40 m3 ha-1 of liquid swine manure) on soil properties and crop production. Soil physical and hydraulic properties and aggregate stability were evaluated at the end of ninth year of the experiment and in five sampling times throughout the tenth year; soil mechanical properties related to soil strength and penetration resistance were determined for some treatments combinations in the tenth year; soil cover, temperature and moisture were determined throughout corn cycle in 2003/2004 crop season, when corn growth and yield were also measured. No-till showed greater bulk density and lower macroporosity and total porosity after tillage and seeding operations, but the differences reduced over time. All tillage systems showed higher compaction degree at depth around 15 cm. Greater mean diameter of air-dry aggregates were found in tillage treatments and layers with higher bulk density, showing close relation between these two parameters. Wet-aggregate stability, on the other hand, was affected by aggregate moisture previous to wet-sieving determination, and greater values were found in tillage treatments where residues were kept in the field. At superficial layer of no-till was observed higher soil strength, as determined by the precompression stress, and to penetration resistance in untrafficked interrow. In seeding row and recent trafficked interrow the differences in penetration resistance among tillage systems were smaller. Higher soil temperature and daily amplitude were found in tilled treatments, mainly at the beginning of corn cycle. After rainfall events, soil moisture reduced faster in chisel plow system, followed by conventional tillage. Higher moisture content and lower water tension was found in no-till system even in long period with hydric deficits, resulting in higher water storage and availability to crops. Higher water availability seems to be the main factor in determining higher crop growth and yield in no-till treatment. Nutrient sources treatments had small effect on physical soil properties, but high effect on chemical properties and crop growth and yield. Greater growth and yield were observed with poultry litter and swine manure application, because of residual and immediate effect of nutrient application through these materials.